Persepsi perawat terhadap upaya pelayanan prima di rumah sakit - Eri Murni Asih; Dessy Hermawan; Teguh Pribadi (Holistik Jurnal Kesehatan, 2020)
Nurses' perceptions of excellent health care servicesBackground: As the spearhead of services to patients and their families at the hospital, nurses have a major influence on determining the quality of services, because the frequency of gathering among nurses, patient and patients family considere the most often. Therefore, a paradigm and mental attitude that is service-oriented are needed, as well as adequate knowledge and skills in carrying out excellent service.Purpose: To describe nurses' perceptions of excellent health care services.Method: An analytical with cross-sectional approach with the number of samples in this study was 53 responden taken by cluster random sampling. teh populations were all staff nurses at Dr. H. Bob Bazar, SKM General Hospital. South Lampung. Data collected through questionnaires and analyzed using univariate analysis, bivariate analysis, and multivariate with SPSS for Windows V. 22.Results: Shows a relationship between perceived susceptibility with excellent service effort (0.021 <0.05), the relationship between perceived severity and excellent service effort (p-value 0.001 <0.05), the relationship between perceived benefit of action and excellent service effort (p-value 0.003 <0.05), the relationship between perceived barrier to action with excellent service efforts at  Dr. H. Bob Bazar, General Hospital South Lampung (p-value 0.007 <0.05), the perceived benefit of action variable is the most dominant variable affecting the prime service effort variable with the Exp value (B) = 46,512.Conclusion: A significant relationship between nurses perceived susceptibility, perceived severity, perceived benefit of action, and perceived of barriers from the action  excellent service at Dr. H. Bob Bazar, SKM General Hospital  South Lampung. The results of this study also found that there was a significant on simultaneous effect of all independent variables on the effort of excellent service.Keywords: Nurses' perceptions; Excellent health care services; HospitalPendahuluan: Sebagai ujung tombak pelayanan terhadap pasien dan keluarganya di Rumah Sakit, perawat memiliki pengaruh besar untuk menentukan kualitas pelayanan, karena kuantitas frekuensi pertemuan perawat dengan pasien dinilai paling sering terjadi. Oleh karena itu, diperlukan paradigma dan sikap mental yang berorientasi melayani, serta pengetahuan dan keterampilan yang memadai dalam melaksanakan pelayanan yang prima.Tujuan: Untuk mengetahui Pengaruh Persepsi Perawat Terhadap Upaya Pelayanan Prima  RSUD dr.H. Bob Bazar, SKM Kabupaten Lampung Selatan.Metode: Penelitian analitik dengan pendekatan cross sectional dengan jumlah sampel sebanyak 53 responden, diambi lsecara clusster random sampling menggunaan rumus slovin. Populasinya seluruh perawat yang bekerja di RSUD dr.H. Bob Bazar, SKM Kabupaten Lampung Selatan. Pengumpulan data melalui kuesioner dan data hasil penelitian dianalisis menggunakan analisis univariat, analisis bivariat, dan multivariat dengan program SPSS for Windows V. 22.Hasil: Menunjukkan hubungan perceived susceptibility dengan upaya pelayanan prima (0,021 < 0,05), hubungan antara (perceived severity dengan upaya pelayanan prima (p-value 0,001 < 0,05), hubungan antara perceived benefit of action dengan upaya pelayanan prima (p-value 0,003 < 0,05), hubungan antara perceived barrier to action dengan upaya pelayanan prima (p-value 0,007 < 0,05), variabel perceived benefit of action merupakan variabel yang paling dominan mempengaruhi variabel upaya pelayanan prima dengan nilai Exp(B)= 46,512.Simpulan: Terdapat hubungan yang signifikan antara persepsi perawat tentang kerentanan/kemungkinan terkena suatu penyakit, persepsi perawat keparahan penyakit, persepsi perawat tentang manfaat dari tindakan, dan persepsi perawat tentang hambatan dari tindakan terhadap upaya pelayanan prima di Rumah Sakit Umum Dr. H. Bob Bazar, SKM Lampung. Terdapat pengaruh bersama secara signifikan seluruh variabel bebas penelitian terhadap upaya pelayanan prima.